Influence of high humidity and salt-rich spray environment on ventilation effect in urban undersea road tunnel - Wang, Xu; Wang, Mingnian; Yu, Li; Tian, Yuan; Yan, Guanfeng (Tunnelling and underground space technology, 2019)
[Display omitted] •A field measurement of jet fan lift in a urban undersea road tunnel was conducted.•The jet fans average lift were attenuated by 12.4% in a corrosive environment.•The ventilation environment in- tunnel will deteriorate with the corrosion of jet fan.•Corrosion reduce jet fan lift by increasing the surface roughness of blades.•The attenuation relationship between jet fan lift and corrosion time is obtained. The urban undersea road tunnels are featured with high frequent traffic congestions and a strict environmental control standard. The internal environment in urban undersea road tunnels is generally controlled by jet fans. The high-humidity, salt-rich spray and acid gas environment in urban undersea road tunnels accelerate the jet fans corrosion, which deteriorates the internal environment and makes the ventilation effect unable to meet the control standards. Detailed examples of pressure drop caused by jet fan corrosion are sparsely available in the publicly available literature. Therefore, this study is to investigate the influence of jet fan corrosion on ventilation effect in urban undersea road tunnel. Based on the Xiamen Xiang’an undersea tunnel, the field measurement of lift produced by jet fan in the tunnel was carried out. Combined with theoretical analysis and Fluent dynamic grid numerical model, the mechanism of reducing lift by jet fan corrosion and the attenuation law of jet fan lift with corrosion time were studied. The results show that salt spray corrosion environment in undersea road tunnel increases surface roughness of the jet fan blades and flow-through components through the effects of accumulation and sedimentation, erosion and corrosion, thereby reducing the lift. After 20 years of operation, the numerical simulated jet fan lift will be reduced by 20.3%, and the ventilation effect will be deteriorate by 20.3% simultaneously. Combined with the field measurement results and the service life of jet fan, the safety factor of ventilation system configuration in undersea tunnel is proposed. Results evidenced that the mechanism of reducing lift by jet fan corrosion in urban undersea road tunnel, which can provide basic data for further research and provide reference for the design of the same type of tunnel ventilation system.